Pharmacists' attitudes toward dispensing naloxone and medications for opioid use disorder: A scoping review of the literature. Issue 4 (2nd October 2019) - Muzyk, Andrew; Smothers, Zachary P. W.; Collins, Kathryn; MacEachern, Mark; Wu, Li-Tzy
Abstract: Background: Pharmacists are on the frontline caring for patients at risk of an opioid overdose and for patients with an opioid use disorder (OUD). Dispensing naloxone and medications for OUD and counseling patients about these medications are ways pharmacists can provide care. Key to pharmacists' involvement is their willingness to take on these practice responsibilities. Methods: The purpose of this scoping review is to identify, evaluate, and summarize published literature describing pharmacists' attitudes toward naloxone and medications for OUD, i.e., methadone, buprenorphine, and naltrexone. All searches were performed on December 7, 2018, in 5 databases: Embase.com, PubMed.gov, Cumulative Index to Nursing and Allied Health Literature (CINAHL) via EBSCOhost, Cochrane Central Register of Controlled Trials via Wiley, and Clarivate Web of Science. Articles included original research conducted in the United States, described attitude-related language toward naloxone and medications for OUD, and pharmacists. Results: A total of 1323 articles were retrieved, 7 were included. Five studies reported on pharmacists' attitudes toward naloxone dispensing, 1 study reported on attitudes toward naloxone, buprenorphine, and buprenorphine/naloxone, and 1 reported on attitudes toward buprenorphine/naloxone. Respondents were diverse, including pharmacists from different practice specialties. Studies found that pharmacists agreed with a naloxone standing order, believed that naloxone should be dispensed to individuals at risk of an opioid overdose, and were supportive of dispensing buprenorphine. A minority of pharmacists expressed negative attitudes. Barriers cited to implementation included education and training, workflow, and management support. Conclusions: Pharmacists were positive in their attitudes toward increased practice responsibilities for patients at risk of an opioid overdose or with an OUD. Pharmacists must receive education and training to be current in their understanding of OUD medications, and they must be supported in order to provide effective care to this patient population.